Serum MOG-IgG in children meeting multiple sclerosis diagnostic criteria. (October 2022) - Fadda, Giulia; Waters, Patrick; Woodhall, Mark; Brown, Robert A; O'Mahony, Julia; Castro, Denise A; Longoni, Giulia; Yeh, E Ann; Marrie, Ruth Ann; Arnold, Douglas L; Banwell, Brenda; Bar-Or, Amit
Background: Myelin oligodendrocyte glycoprotein antibody-associated disease (MOGAD) is now recognized as distinct from multiple sclerosis (MS). Objective: To evaluate the importance of considering myelin oligodendrocyte glycoprotein (MOG)-immunoglobulin-G (IgG) serology when applying MS diagnostic criteria in children. Methods: Within a prospective cohort of children meeting MS criteria (median follow-up = 6 years, interquartile range (IQR) = 4–9), we measured MOG-IgG in serial archived serum obtained from presentation, and compared imaging and clinical features between seropositive and seronegative participants. Results: Of 65 children meeting MS criteria (median age = 14.0 years, IQR = 10.9–15.1), 12 (18%) had MOG-IgG at disease onset. Seropositive participants were younger, had brain magnetic resonance imaging (MRI) features atypical for MS, rarely had cerebrospinal fluid (CSF) oligoclonal bands (2/8, 25%), and accumulated fewer T2 lesions over time. On serial samples, 5/12 (42%) were persistently seropositive, 5/12 (42%) became seronegative, and 2/12 (17%) had fluctuating results. All 12 children experienced a disease course different from typical MS. Conclusion: While children with MOG-IgG can have clinical, CSF, and MRI features conforming to MS criteria, the presence of MOG-IgG is associated with atypical features and predicts a non-MS disease course. Given MOG-IgG seropositivity can wane over time, testing at first attack is of considerable importance for the diagnosis of MOGAD.